3D model construction and processing - Zhang, Jiawei (2014)
This project aims to decompose and reconstruct 3D models in STL format for display, slicing, meshing, storage as well as processing. The technique called voxelization is used to convert the STL format triangular mesh information into solid regular cube array, so that the layer image can be exported easily for further processing. Changing size, adding color information, a few image processing work are conducted to the layers in this project. And a commonly utilized method, checking isosurface, is adopted to reconstruct 3D model. The entire project is completed basically in a program running under the circumstance of Matlab. Also some software is used in this project for preliminary work and comparison.